BANK BRI KC SURABAYA KERTAJAYA: MITRA STRATEGIS UNTUK UMKM DAN INDIVIDU - Ida Ayu Nuh Kartini; Kharin Dinda Aisyah; Johana Rizky Widyastuti; Jessicka Amelia Joyta; Fitra Aoelintiano Nico Victorian (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the post-pandemic economic landscape, the banking industry faces a dual challenge: accelerating digital transformation while maintaining inclusivity for the unbanked sector. This study investigates the strategic role of Bank BRI Branch Office (KC) Surabaya Kertajaya in empowering Micro, Small, and Medium Enterprises (MSMEs) and individuals within the Surabaya ecosystem, specifically at Pasar Pucang Anom. Adopting a descriptive qualitative approach with simulated field observations and in-depth interviews, this research explores the implementation of the